PENGARUH PENERAPAN MODEL RECIPROCAL TEACHING TERINTEGRASI MIND MAPPING TERHADAP PEMAHAMAN KONSEP SISWA PADA MATERI FILUM ARTHROPODA - Nurmasari Sartono; Ratna Komala; Helda Dumayanti (Biosfer: Jurnal Pendidikan Biologi, 2016)
The Arthropoda Phyllum is part of the Biology subject that requires an understanding of concepts. One of models for these subject is a reciprocal teaching integrated mind mapping model. This model make the students better to understand and easier to remember it for the relationship between various concepts, and their visualization and image colours. The purpose of this research was to know the effect of reciprocal teaching integrated mind mapping model application towards to student’s understanding concept on Arthropoda Phyllum. The research was conducted in SMA 105 Jakarta from February until March 2016. The research method was used a quasi-experimental with research design posttest-only control group design. Sample handling technical was used simple random sampling method. The instrument of these method was comperehension concept posttest in the form of multiple choice objective test accompanied by CRI index (Certainty of Response Index) or the scale of confidence of respondents in answering questions. Based on data analysis result, showed that data as normally distributed and homogeny. The conclusions of this research show there is effect of application reciprocal teaching integrated mind mapping model toward student’s comperehension concept on Phyllum Arthropoda.